2015
DOI: 10.1021/acs.est.5b02560
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Liquid/Gas Mass-Transfer Limitations to Dissolved Methane Oversaturation in Anaerobic Treatment of Dilute Wastewater

Abstract: The mechanisms controlling the accumulation of dissolved methane in anaerobic membrane bioreactors (AnMBRs) treating a synthetic dilute wastewater (a glucose medium) were assessed experimentally and theoretically. The AnMBR was maintained at a temperature of 24-26 °C as the organic loading rate increased from 0.39 to 1.1 kg COD/m(3)-d. The measured concentration of dissolved methane was consistently 2.2- to 2.5-fold larger than the concentration of dissolved methane at thermodynamic equilibrium with the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 33 publications
(81 reference statements)
2
22
0
2
Order By: Relevance
“…Which parameters mainly influence oversaturation of aqueous methane in liquid? Yeo et al (2015) developed an equation for dissolved methane concentration at a steady-state bioreactor.…”
Section: Dissolved Methanementioning
confidence: 99%
See 1 more Smart Citation
“…Which parameters mainly influence oversaturation of aqueous methane in liquid? Yeo et al (2015) developed an equation for dissolved methane concentration at a steady-state bioreactor.…”
Section: Dissolved Methanementioning
confidence: 99%
“…The first issue is accumulation of dissolved methane in AnMBR permeates. Literature reported dissolved methane concentration ranges from 16 to 35.1 mg/L (Kim et al, 2011; Yeo et al, 2015; Yoo et al, 2012), indicating methane loss up to 63% in AnMBR systems. Methane loss as aqueous methane decreases economic return from reuse of methane gas, which indicates that the economic benefit in AnMBRs could be small; consequently energy neutrality could not be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…During AnMBR treatment, the CH4 yield increases linearly with the organic loading rate (Yeo et al, 2015). Under an optimized condition, AnMBR can convert up to 98% of the influent COD into biogas, which is equivalent to seven times of the energy…”
Section: Biogas Productionmentioning
confidence: 99%
“…The rate of CH 4 production in R DW was 0.29 ± 0.06 mmol l À1 influent (equal to 2.32 mmol electrons l À1 influent), which was much lower than that in R Glu (0.50 ± 0.07 mmol l À1 influent or 4.00 mmol electrons l À1 influent) and R Ac (1.26 ± 0.02 mmol l À1 influent or 10.08 mmol electrons l À1 influent). The dissolved CH 4 (Table 2) were estimated according to the Henry's law based on the CH 4 volume fraction in gas phases (Sander, 2015;Yeo et al, 2015) (details can be found in SI). In addition to methanogenesis, electrons can be also used to supporting bacteria growth.…”
Section: Decolorization Performance With Domestic Wastewater As Electmentioning
confidence: 99%
“…COD consumptions and reductant usage ratios (RURs) of domestic wastewater, NaAc and glucose feeding BESs at different loading rates. (Sander, 2015;Yeo et al, 2015).…”
Section: Decolorization Performance With Decreasing Electron Donor Somentioning
confidence: 99%